Solubility enhancement of carvedilol using drug-drug cocrystallization with hydrochlorothiazide - Shivarani Eesam; Jaswanth S. Bhandaru; Chandana Naliganti; Ravi Kumar Bobbala; Raghuram Rao Akkinepally (SpringerOpen, 2020)
Abstract Background Increasing hydrophilicity of poorly water-soluble drugs is a major challenge in drug discovery and development. Cocrystallization is one of the techniques to enhance the hydrophilicity of such drugs. Carvedilol (CAR), a nonselective beta/alpha1 blocker, used in the treatment of mild to moderate congestive heart failure and hypertension, is classified under BCS class II with poor aqueous solubility and high permeability. Present work is an attempt to improve the solubility of CAR by preparing cocrystals using hydrochlorothiazide (HCT), a diuretic drug, as coformer. CAR-HCT (2:0.5) cocrystals were prepared by slurry conversion method and were characterized by DSC, PXRD, FTIR, Raman, and SEM analysis. The solubility, stability, and dissolution (in vitro) studies were conducted for the cocrystals. Results The formation of CAR-HCT cocrystals was confirmed based on melting point, DSC thermograms, PXRD data, FTIR and Raman spectra, and finally by SEM micrographs. The solubility of the prepared cocrystals was significantly enhanced (7.3 times), and the dissolution (in vitro) was improved by 2.7 times as compared to pure drug CAR. Further, these cocrystals were also found to be stable for 3 months (90 days). Conclusion It may be inferred that the drug-drug (CAR-HCT) cocrystallization enhances the solubility and dissolution rate of carvedilol significantly. Further, by combining HCT as coformer could well be beneficial pharmacologically too.